Assessment of Knowledge, Attitude, and Practice of Risky Sexual Behavior Leading to HIV and Sexually Transmitted Infections among Egyptian Substance Abusers: A Cross-Sectional Study. (25th August 2014) - Bakhoum, Atef Y.; Bachmann, Max O.; El Kharrat, Ehab; Talaat, Remon
Abstract : Background . Rapidly growing youth population with changing sexual trend in Egypt raised HIV potential. The aim of this study is to assess knowledge, attitude, and practice regarding unsafe sexual behavior among Egyptian drug abusers. Methods . This cross-sectional study was conducted in 2008 in the Freedom Drugs and HIV Program on 410 drug abusers in Egypt. Included respondents were subanalyzed by gender, age, education, and intravenous drug usage. Results . KAP average scores on safe sexual behavior were low compared to the maximum possible denoting low awareness and action of drug addicts towards avoidance of infection. Respondents with higher education had significantly better knowledge about safe sexual behavior. Significant positive correlation was shown between age and knowledge of safe sexual behavior. Older age groups were predicted to know more about safe sex, while gender; educational level and intravenous drug usage were not. Similarly, females and intravenous drug users were predicted to have higher attitude for safe sex while age and educational level did not. Conclusion . KAP of safe sexual behavior were low among drug addicts in Egypt increasing potential towards infection with STDs including HIV. The more the age and education level, the better the knowledge towards safe sexual behavior.